STEIN, WOOLF, AND JOYCE: MODERNIST AUTHORS ON CHILDREN’S BOOKSHELVES - Magri, Guilherme; Navas, Diana (Revista de Letras Norte@mentos, 2025)
This article examines how the works of Gertrude Stein, James Joyce, and Virginia Woolf have been published, adapted, and reimagined, and how they circulate within children’s literature. The study introduces and briefly discusses a corpus that includes original texts written for children, picturebooks, fictionalized biographies, and graphic novels. It argues that these texts defy rigid distinctions between adult and children’s literature and promote crossover reading modes by offering layered narratives that resonate differently with children and adults. Younger readers encourage imaginative engagement and play; adult readers, particularly educators, scholars, or enthusiasts, provide intertextual depth and cultural criticism. The findings affirm that the modernist legacy has extended beyond its canonical borders through creative repackagings that reframe reading as a dynamic, inclusive, and age-transcendent experience.